Analysis of the Practice of Buying and Selling Household Appliances in Accordance with Sharia Economic Law - Nurfaza, Arina; Zahwati, Roza (International Journal of Management Science and Information Technology, 2024)
This research discusses early billing that is not in accordance with the escort agreement according to sharia economic law. Using a descriptive qualitative method of interview as a primary data source, the research found that there is a practice of the seller billing the buyer early, namely every 10th of the month of the agreement, the billing should be agreed upon on the 25th. 2. Analysis of the practice of buying and selling household appliances according to sharia economic law in the city of Subulussalam is not valid, because the terms and conditions of buying and selling have not been fulfilled. Because it is not in accordance with the initial agreement that has been mutually agreed between the seller and the buyer.